Management of Orobanche in mustard - Dixit, Anil; Chaudhary, V. K.; Rajendran, T. P. (Indian Farming, 2015)
Orobanche, or broomrape is a complete root parasite in mustard,tobacco, tomato, brinjal, potato etc. Various management practices are available to stop the menace of this parasite to check a huge economic loss of the crop.